The Historical Development of Islamic Scholarly Thought and Literature on the Qur’an’s Miraculous Nature (Iʿjāz al-Qur’ān) - Oktafiani, Shalsabila; Basri, Halimah; Mujahid, Ahmad (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
The Miraculous Nature of the Qur’an has remained one of the central themes in Islamic studies throughout history. Over time, the understanding of this miraculous nature has evolved, influenced by the social, cultural, and intellectual contexts in which scholars lived and produced their works. This study aims to examine the dynamics of thought regarding the Qur’an’s miraculousness by analyzing the works of scholars from three significant periods: classical, medieval, and contemporary. The method employed is a qualitative-descriptive library study, focusing on the works of al-Jurjānī, al-Suyūṭī, Mannā‘ al-Qattān, and Quraish Shihab as representatives of each respective era. The findings reveal that although these scholars emphasize different aspects in their interpretations of the Qur’an’s miraculousness, they all begin from a shared conviction that the Qur’an possesses an unmatched uniqueness. This study concludes that such differences in perspective reflect the intellectual richness of Islamic thought—complementary rather than contradictory. The contribution of this research lies in its effort to map and elucidate the diversity of scholarly approaches to the theme of miraculousness, as well as to encourage the development of Qur’anic studies that are more contextual, open, and responsive to contemporary challenges.